Systematics of the Dendropsophus leucophyllatus species group (Anura, Hylidae) from the Chocó region of Ecuador, with description of a new species - P. Doménica Aguirre; Katherine Apunte; Santiago R. Ron (Evolutionary Systematics, 2025)
The Dendropsophus leucophyllatus group is composed by 19 species distributed from Central America to the Atlantic Forest of Brazil. Only one species is known from the Chocó region, D. ebraccatus, which is also distributed in Central America. Previous studies suggested the existence of two species masked under “D. ebraccatus”. The only other species of Dendropsophus in the Chocó lowlands of Ecuador is D. gryllatus, an elusive species never included in phylogenetic analyses. In the present study, we review the systematics of both species based on morphological, genetic, and bioacoustic data. For phylogenetic analyses, we sequenced four mitochondrial genes (12S, 16S, COI, ND1, including flanking tRNAs) and two nuclear genes (TYR, POMC). Our results indicate that the populations of “D. ebraccatus” from the Chocó of Ecuador represent a new species, not most closely related to D. ebraccatus from Central America, but to D. gryllatus. The new species inhabits tropical rainforest and piedmont evergreen forest of NW Ecuador and SW Colombia. Populations of the new species differ from D. gryllatus by having larger body size and by the presence of an hourglass-shaped dorsal mark. The new species differs from D. ebraccatus from Central America by the absence of a clear band under the eye, by having well defined dorsal spots and by having a distinct advertisement call. Both species appear to be allopatric and, according to our time-tree, diverged from each other during the late Pliocene.